Land Use Program for Hydroponic Cultivation of Women Farmer Groups (KWT) Anggraeni Clumprit Gerbosari Samigaluh Kulon Progo - Muhammad Nizar Hasan; Achmad Ibnu Masngud; Muhammad Wahyudi (Kaunia: Integration and Interconnection Islam and Science, 2018)
Community service program in the form of hydroponic cultivation of land use programs by Women Farmer Groups Anggraeni in Clumprit, Gebosari, Samigaluh, Kulon Progo is expected to be an alternative for society who have limited land so that they can be used as a source of sufficient income. Hydroponics is a method of farming using planting media in the form of pumice, gravel, sand, coconut fiber, pieces of wood and foam.  This has implemented as the function of the soil is to support plant roots and intermediate nutrient solutions can be replaced by flowing or adding nutrients, water and oxygen through these media. Counseling of this programs received good responses from the community. This is proven by the high level of community participation.